Electronic Toll Payment System Using RFID Smart Card - Badrul Hisham, Mohd Irfan (Universiti Teknologi PETRONAS, 2009)
This Degree's Final Year Projectpresents RFIDpaymentsystemto be appliedto the car toll collection system. Theproject is entitled "Electronic Toll Payment System Using RFIDSmartCard".The objectives are to develop an electronic smart card integratedwith RFIDtechnology and prepaid features for toll farepaymentpurposes. Project's prototype will providea suitable, fast and up to date technology in collecting toll fare. In actual simulation, it doesn't required interaction between the car ownerandthe toll but only need the car to pass toll gantry where RFID reader will detect RFID smart card and toll farepaymentwill be madeautomatically. Hence, creatingan alternative solution for Toll Company whichcurrently using ticketingtechnology and facing traffic control issues during peakhours. Implementation procedure for this prototype in daily activities, RFID tag serves concurrently as smart cardimproving current automatic toll payment system, i.e. TouchN' Go. This tag can be programmed to saveuniqueidentifier(UID)that determines vehicle information details, retrieved from central database. IV